2022
DOI: 10.1021/acs.jafc.2c05562
|View full text |Cite|
|
Sign up to set email alerts
|

Co-production of l-Lysine and Heterologous Squalene in CRISPR/dCas9-Assisted Corynebacterium glutamicum

Abstract: Corynebacterium glutamicum is widely used for a large-scale industrial producer of feed additive amino acids, such as Llysine. Moreover, C. glutamicum has been engineered for producing various non-native chemicals, including terpenes. For the first time, C. glutamicum was engineered for co-production of L-lysine and heterologous squalene. To control metabolic fluxes for either the L-lysine biosynthesis pathway or the squalene biosynthesis pathway, pyruvate, an intermediate in the central metabolism, a node was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…14 Previous studies have shown that 99.24 ± 7.63 mg/L intracellular squalene and 6.25 ± 0.20 g/L extracellular lysine can be obtained by a single fermentation of Corynebacterium glutamicum using a coproduction strategy. 15 The coproduction of polyhydroxyalkanoates (PHAs) with other valuable chemicals has been used to reduce the cost of PHA production. 16 These recent developments motivated our attempts to develop an erythritol-producing yeast platform for β-carotene coproduction at a low cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Previous studies have shown that 99.24 ± 7.63 mg/L intracellular squalene and 6.25 ± 0.20 g/L extracellular lysine can be obtained by a single fermentation of Corynebacterium glutamicum using a coproduction strategy. 15 The coproduction of polyhydroxyalkanoates (PHAs) with other valuable chemicals has been used to reduce the cost of PHA production. 16 These recent developments motivated our attempts to develop an erythritol-producing yeast platform for β-carotene coproduction at a low cost.…”
Section: Introductionmentioning
confidence: 99%
“…The perspective of coproduction processes has potential since the engineered microbes capable of simultaneously accumulating multiple products are economically appealing for biotechnology . Previous studies have shown that 99.24 ± 7.63 mg/L intracellular squalene and 6.25 ± 0.20 g/L extracellular lysine can be obtained by a single fermentation of Corynebacterium glutamicum using a coproduction strategy . The coproduction of polyhydroxyalkanoates (PHAs) with other valuable chemicals has been used to reduce the cost of PHA production .…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, we aimed to further increase geranoid titers by reducing downstream consumption of IPP and DMAPP by competing metabolic pathways. Previous efforts to decrease the flux of IPP and DMAPP into competing carotenoid biosynthetic pathways by targeting two geranylgeranyl diphosphate synthases, CrtE and IdsA, led to an increase in valencene and squalene production in C. glutamicum (Frohwitter et al 2014; Park and Woo 2022) . Interestingly, iteratively targeting crtE and idsA in strains harboring either pBAL114 or pBAL218 resulted in opposite effects on titers (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it possesses superior recombinant protein expression due to its minimal protease activity as well as the ability to assimilate multiple carbon sources in a monoauxic growth state (Ray et al 2022). However, despite its keys advantages and impressive natural product repertoire, only a limited set of isoprenoids have been produced in C. glutamicum (Moser and Pichler 2019; Heider and Wendisch 2015; Park and Woo 2022; Henke et al 2018; Frohwitter et al 2014; H. Lim, Park, and Woo 2020; Li, Xu, and Lu 2021) .…”
Section: Introductionmentioning
confidence: 99%